Impact Analysis of Physical Violence on Women (Research Nepal Journal of Development Studies, 2018)
Women, constituting of more than 50% of total population of the world devote their life for their family as well as children. They are the center of love and affection; the main candle of light in family as well as in nation. Despite their high value, they are being mistreated by many peoples in the world leading to the devastating social structure. The violence against women being both fatal as well as non-fatal, can bring devastation in the life as well as structure of individual and society and has taken its toll as a cancer that is spreading from within and thus is decreasing the productivity of the world and exposing whole world to vulnerability. The physical violence on women can be a major gateway for the entry of other major health related as well as lifestyle related difficulties. Violence is the act of forcing someone into doing something that they don’t like as well as stopping them from doing something that they like. The activity that promotes violent act to women is considered as violence against women. The violence against women can cause various issues such as economic issue, social issue, morbidity issue, and psychological issue. The terrific situation of physical violence against women has to be resolved in time for the system to be able to function in the desired way. For the completion of this research, secondary data has been used in the analysis field so that the result of physical violence can be enlightened.